The impact of thyroid disorder on cardiovascular disease: Unraveling the connection and implications for patient care - Nanny Natalia Mulyani Soetedjo; Dessy Agustini; Hikmat Permana (International Journal of Cardiology: Heart & Vasculature)
The thyroid gland is responsible for metabolism, as well as cardiac function and the peripheral vascular system. Thyroid dysfunctions are associated with an increase in the risk of cardiovascular diseases, including heart failure and coronary heart disease atrial fibrillation, by impairing heart contractility, stroke volume, heart rate, peripheral vascular resistance, and electrical activity. Thyroid dysfunctions also alter several cardiovascular risk factors, such as atherosclerosis, hypertension, and dyslipidemia, as well as causing stroke, which is associated with atrial fibrillation. An antiarrhythmic drug, amiodarone, may also induce both thyrotoxicosis and hypothyroidism, so its use requires serial thyroid function testing. Every CVD patient is recommended to be screened and treated for any possible thyroid dysfunction to reduce the patient’s mortality and morbidity.